DIAGNOSTIC AND MANAGEMENT OF PATIENT WITH ADRENOCORTICAL CARCINOMA - Mamluatul Karimah (Universitas Airlangga, 2021)
Endogenous Cushing’s syndrome is a rare case, and about 8% is due to adrenocortical carcinoma. We report a case of a 31-year-old womanwith complaints of weight gain, round face, brown lines, menstrual disorders, and limb weakness. On physical examination, there werehypertension, moon face, central obesity, and stroke. On laboratory examination, there were morning serum cortisol levels were 46.87 andACTH levels 5. On CT scan. It was found that the right adrenal gland solid mass enhancement was +/- 6.6x4.9x7.3 cm, with suspicion ofadrenal carcinoma. On histopathological examination, adrenocortical carcinoma was obtained, and capsule invasion was obtained. Patients underwent surgery to remove the tumor, radiotherapy and chemotherapy. The patient was alive and had no residual mass at the surgical bed.